2015
DOI: 10.1007/s10120-015-0471-6
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic impact of HER2, EGFR, and c-MET status on overall survival of advanced gastric cancer patients

Abstract: Background This study was conducted to investigate whether human epidermal growth factor receptor 2 (HER2) status, epidermal growth factor receptor (EGFR) status, and c-MET status are independent prognostic factors for advanced gastric cancer patients who received standard chemotherapy. Method Unresectable or recurrent gastric or gastroesophageal junction cancer patients with histologically confirmed adenocarcinoma treated with S-1 plus cisplatin as first-line chemotherapy were eligible. Formalin-fixed paraffi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
69
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(75 citation statements)
references
References 37 publications
4
69
2
Order By: Relevance
“…Epidermal growth factor receptor (EGFR) overexpression was observed in 27%-44% of primary gastric tumors, and is reported to be an indicator of poor prognostic outcome and, hence, an important therapeutic target. 4 Cetuximab (CET; Erbitux ® , Merck, Darmstadt, Germany) is a chimeric IgG monoclonal antibody (MAb) approved by the US Food and Drug Administration for colorectal carcinoma and head and neck cancers that has also shown clinical benefit toward advanced/metastatic gastric adenocarcinoma in combination with other chemotherapeutic agents as a first-line treatment. [5][6][7] Researchers have been interested in exploring anticancer formulations in the form of nanomedicines, either as a combination of multiple drugs loaded into nanocarriers (combinatorial nanomedicines) or as drug-loaded nanocarriers that are actively targeted to specific overexpressed surface receptors such as EGFR (targeted nanomedicines) to improve the anticancer potential.…”
Section: Introductionmentioning
confidence: 99%
“…Epidermal growth factor receptor (EGFR) overexpression was observed in 27%-44% of primary gastric tumors, and is reported to be an indicator of poor prognostic outcome and, hence, an important therapeutic target. 4 Cetuximab (CET; Erbitux ® , Merck, Darmstadt, Germany) is a chimeric IgG monoclonal antibody (MAb) approved by the US Food and Drug Administration for colorectal carcinoma and head and neck cancers that has also shown clinical benefit toward advanced/metastatic gastric adenocarcinoma in combination with other chemotherapeutic agents as a first-line treatment. [5][6][7] Researchers have been interested in exploring anticancer formulations in the form of nanomedicines, either as a combination of multiple drugs loaded into nanocarriers (combinatorial nanomedicines) or as drug-loaded nanocarriers that are actively targeted to specific overexpressed surface receptors such as EGFR (targeted nanomedicines) to improve the anticancer potential.…”
Section: Introductionmentioning
confidence: 99%
“…76,77 EGFR copy number gains associate with an increased risk of invasion and metastasis in solid tumors including GC, suggesting its potential significance as a prognostic marker. [78][79][80][81] As reported, there is a strong relationship between EGFR gene copy number, protein expression and chromosome 7 polisomy. 82 Oh et al 83 further observed that EGFR CNVs existed in a series of GC cases and discovered that it was associated with unfavorable prognosis.…”
Section: Chromosomementioning
confidence: 92%
“…EGFR signaling can involve a number of intracellular molecules such as extracellular signal-regulated kinase (ERK), cyclin D1 and β-catenin [51]. The presence of EGFR is detected in a wide range of cancer types (Table 3 [51], [52], [53], [54], [55], [56], [57], [58], [59], [60], [61], [62], [63], [64], [65], [66], [67], [68], [69], [70], [71], [72], [73], [74], [75], [76], [77]). Normally, the EGFR gene is located on chromosome 7.…”
Section: The Egfr and Its Familymentioning
confidence: 99%